Red, white, and black: the peoples of early America - Nash, Gary B. (Englewood Cliffs, N.J., Prentice-Hall, 1974)
A history text of America's colonial period emphasizing the interaction of three cultures--colonialists, Indians, and blacks.
Bibliography: p. 320-341.
Keywords: United States -- History -- Colonial period, ca. 1600-1775.; America -- Discovery and exploration; United States -- Race relations